Review of acoustical methods of probing the atmoshperic boundary layer - FORTUNA, J.; KOZACZKA, E. (Archives of Acoustics, 1992)
The paper presents the review of the methods of remote probing of the lower atmosphere by using the acoustic sounders. Sodar's constructions, their possibilities and usefulness are also presented. By leading to an understanding of the mechanisms underlying the origin of acoustic echoes, sodars provide new insight into the physical processes affecting the lower atmosphere.